تأثير العوامل المتعلقة بالعميل على قرار منح الائتمان الصغير دراسة ميدانية على المؤسسات الإقراضية الخاصة العاملة في محافظة اللاذقية. (Latakia University Journal - Economic and Legal Sciences Series, 2016)
هدفت هذه الدراسة إلى التعرف على العوامل الخاصة بالعميل (طالب الائتمان) والمؤثرة على قرار منح الائتمان في المؤسسات الإقراضية الخاصة العاملة في محافظة اللاذقية (المصارف الخاصة ومؤسسات التمويل الصغير)، وترتيب هذه العوامل حسب الأهمية بالنسبة لهذه المؤسسات، وقد تم اتباع المنهج الوصفي المسحي في هذه الدراسة.وتوصل البحث إلى أن هذه المؤسسات تركز على شخصية العميل بالدرجة الأولى ثم رأسمال العميل بالدرجة الثانية ثم الضمانات المقدمة من العميل بالدرجة الثالثة، كما بينت النتائج أن الظروف الاقتصادية والسياسية والخبرة العملية للعميل تؤثر على قرار منح الائتمان بدرجة ضعيفة نسبياً، وهناك إغفال للعامل الاجتماعي من قبل هذه المؤسسات.This study aims to identify the factors related to the client and influencing the decision of granting micro-credit in the private lending institutions operating in the province of Lattakia (Private banks and microfinance institutions)، and order of these factors according to their importance for these institutions، Has been followed premise entrance deductive in this study.The research concluded that these institutions focus on personal client primarily client then the capital of the second class، then the guarantees provided by the client third place، as the results showed that the economic and political conditions and practical experience for the customer influence the decision to grant credit is relatively weak degree، and there omission social worker by these institutions.